High‐Water Marks and Hedge Fund Management Contracts - Goetzmann, William N.; Ingersoll, Jonathan E.; Ross, Stephen A. (Journal of Finance, 2003)
ABSTRACT Incentive fees for money managers are frequently accompanied by high‐water mark provisions that condition the payment of the performance fee upon exceeding the previously achieved maximum share value. In this paper, we show that hedge fund performance fees are valuable to money managers, and conversely, represent a claim on a significant proportion of investor wealth. The high‐water mark provisions in these contracts limit the value of the performance fees. We provide a closed‐form solution to the cost of the high‐water mark contract under certain conditions. Our results provide a framework for valuation of a hedge fund management company.